Isolation and characterization of astaxanthin-hyperproducing mutants of Haematococcus pluvialis (Chlorophyceae) produced by dielectric barrier discharge plasma. Issue 6 (1st November 2016) - Liu, Jinghua; Chen, Jun; Chen, Zhu; Qin, Song; Huang, Qing
Abstract: Haematococcus pluvialis has potential commercial application for its ability to accumulate astaxanthin under stress conditions. To improve astaxanthin productivity, nonthermal plasma can be used to produce mutant algal strains with enhanced production of astaxanthin. In this work, atmospheric pressure argon dielectric barrier discharge (DBD) was used for mutation induction. Several new algal strains with increased growth rate and higher astaxanthin accumulation were obtained. For analysis of the DBD-treated algal mutants, genetic variation was examined by random amplification of polymorphic DNA, and the pigment pattern in response to inhibitors (diphenylamine and nicotine) of carotenoid biosynthetic pathway was characterized by high-performance liquid chromatography. Furthermore, photosynthetic activity and gene expression were also examined by pulse amplitude-modulated fluorometry and quantitative real-time polymerase chain reaction, respectively. Our results confirmed that the enhanced astaxanthin accumulation in the mutants was associated with increased expression levels of lycopene cyclase, which is involved in the conversion of lycopene to β-carotene. As such, this work demonstrates a successful example for the effective application of DBD in the mutation breeding of astaxanthin-hyperproducing algal strains.